Kepedulian Remaja Dalam Menjaga Kebersihan Lingkungan di Kelurahan Piai Tangah Kecamatan Pauh Kota Padang. - Darmayanti, Tuti - (STKIP PGRI Sumbar, 2014)
This study aimed to obtain the data, process, analyze and discuss in Keeping Teens Health Care Environment in Sub Piai Tangah Padang Pauh subdistrict. This research is descriptive. The study population was a teenager in the Village Piai Tangah Padang Pauh subdistrict totaled 576 people. The sample of respondents in this study amounted to 113 people were taken by means of proportional random sampling technique. The instrument used in this study was a questionnaire. Analysis of the data using a percentage formula. Based on the analysis of the data obtained on the findings that: 1) Concern teens in keeping the environment in Sub Piai Tangah Padang Pauh subdistrict in keeping the environment can be considered quite good (44.95%). 2) Concern teens in keeping the environment in Sub Piai Tangah Padang Pauh subdistrict in the use of the environment can be considered quite good (46.27%). 3) Concern teenagers in keeping the environment in Sub Piai Tangah Padang Pauh subdistrict in environmental regulation can be said to be already quite good (48.59%). 4) Concern teens in keeping the environment in Sub Piai Tangah Padang Pauh subdistrict in the maintenance of the environment can be considered quite good (48.14%).